Analysis of the content of art education curriculum for the first-grade primary in the light of multiple intelligences strategy - Al-Harbi, Amani Mohamed (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the degree of inclusion of multiple types of intelligence in the content of the art education curriculum sample, identify the distribution and balance of the indicators of multiple types of intelligence in the content of the art education curriculum sample, and identify the degree of inclusion of multiple types of intelligence in the content of the study sample, namely: (lesson preparation, lesson objectives, lesson presentation procedures). The researcher followed the descriptive analytical approach through analyzing the content represented in (the teacher/ teacher guide) for the art education curriculum, the first semester and revealing the degree of inclusion of multiple types of intelligence in the content of the study sample, namely: (preparation for the lesson, objectives of the lesson, procedures for presenting the lesson) and designed the researcher The content analysis list includes the seven specific types of intelligence (visual, linguistic, social, motor, environmental, personal, and logical intelligence) and indicators of each intelligence in the three curricular units (line and shape unit, color unit, flat and stereoscopic unit). The study showed the following: 1) There is a variation in the degrees of repetition observed for the seven components of intelligence in (line and shape) unit, and the logical intelligence index appeared high (17.70%), and low in motor intelligence (7.08%). 2) In (color) unit, the social intelligence index appeared high (18.18%), and there is a decrease in kinetic intelligence by (7.07%). 3) In (flat and stereoscopic formation) unit, the logical intelligence index appeared high (17.39%), and there is a decrease in kinetic intelligence (5.22%). The results also showed there is an imbalance between the components of intelligence with the content of the curriculum sample (The three units) with a high percentage of logical intelligence (17.13%) and low in motor intelligence by (6.42%). This contradicts with what the multiple intelligence theory emphasized regarding the necessity of balance and symmetrical distribution of intelligence with each other. In light of results, the study recommended the necessity of adopting the multiple intelligences theory in writing the content of art education curricula for the elementary stage.
Keywords: Content Analysis; Curriculum for Art Education; First Primary Class; Multiple Intelligence Theory